2010
DOI: 10.1144/0016-76492010-050
|View full text |Cite
|
Sign up to set email alerts
|

Modern seawater acidification: the response of foraminifera to high-CO 2 conditions in the Mediterranean Sea

Abstract: The seas around the island of Ischia (Italy) have a lowered pH as a result of volcanic gas vents that emit carbon dioxide from the sea floor at ambient seawater temperatures. These areas of acidified seawater provide natural laboratories in which to study the long-term biological response to rising CO 2 levels. Benthic foraminifera (single-celled protists) are particularly interesting as they have short life histories, are environmentally sensitive and have an excellent fossil record. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 26 publications
13
88
1
Order By: Relevance
“…Species-specific responses have been confirmed in a study by Hikami et al (2011). Studies of Foraminifera from natural CO 2 seeps with locally decreased pH reported increasing incidences of altered shell structure, decreasing population densities, declining diversity in calcifying Foraminifera, and increasing proportion of Foraminifera with agglutinated shells towards low pH/high pCO 2 (Dias et al 2010;Fabricius et al 2011;Uthicke and Fabricius 2012;Uthicke et al 2013). Test dissolution has been reported under elevated pCO 2 (Sinutok et al 2011).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Species-specific responses have been confirmed in a study by Hikami et al (2011). Studies of Foraminifera from natural CO 2 seeps with locally decreased pH reported increasing incidences of altered shell structure, decreasing population densities, declining diversity in calcifying Foraminifera, and increasing proportion of Foraminifera with agglutinated shells towards low pH/high pCO 2 (Dias et al 2010;Fabricius et al 2011;Uthicke and Fabricius 2012;Uthicke et al 2013). Test dissolution has been reported under elevated pCO 2 (Sinutok et al 2011).…”
Section: Introductionmentioning
confidence: 76%
“…However, the fact that in both studied species, growth was inhibited in the combined treatment indicates that in the long term, growth and by inference calcification under lower saturation may become more difficult. This may ultimately lead to ecological exclusion of these species as observed at present in CO 2 seep systems (Dias et al 2010;Uthicke and Fabricius 2012;Uthicke et al 2013). …”
Section: Discussionmentioning
confidence: 98%
“…This is in accordance with our conclusion based on the correlation between SNW, growth rates and carbonate ion concentration. Up to now it remains unclear whether reduced calcification will affect the survival of foraminifera in the future, but evidence has been provided from naturally CO 2 -rich environments (Fabricius et al, 2011;Dias et al, 2010) that a reduction in foraminiferal diversity and abundance is associated with high pCO 2 /low [CO 2− 3 ] levels. This could potentially affect marine ecosystems and oceanic uptake of atmospheric CO 2 , since a reduction in planktonic foraminiferal ballast would reduce organic carbon export to deeper waters (Passow, 2004).…”
Section: Implications For Foraminiferal Calcificationmentioning
confidence: 99%
“…Gao et al 1993, 2009, Langdon et al 2000, Langdon & Atkinson 2005, Anthony et al 2008, Kuffner et al 2008, Zheng & Gao 2009, Kleypas & Yates 2009, Dias et al 2010, Dupont et al 2010, Gao & Zheng 2010, Diaz-Pulido et al 2012, Hofmann et al 2012. Within the marine environment, different biogenic polymorphs of CaCO 3 are deposited, each with different solubility in seawater (Ries 2011).…”
Section: Introductionmentioning
confidence: 99%